Dance, Philosophy, and Somaesthetics - Eric Mullis (Performance Philosophy, 2016)
This essay examines the question whether dance can do philosophy by considering the manner in which dance processes used in the studio can advance philosophical investigations of human embodiment.  Two contemporary improvisation techniques are discussed, Gaga technique developed by Ohad Naharin and Contact Improvisation developed by Steve Paxton.